2010
DOI: 10.1073/pnas.1000473107
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3b recruitment through E2F6 transcriptional repressor mediates germ-line gene silencing in murine somatic tissues

Abstract: Methylation of cytosine residues within the CpG dinucleotide in mammalian cells is an important mediator of gene expression, genome stability, X-chromosome inactivation, genomic imprinting, chromatin structure, and embryonic development. The majority of CpG sites in mammalian cells is methylated in a nonrandom fashion, raising the question of how DNA methylation is distributed along the genome. Here, we focused on the functions of DNA methyltransferase-3b (Dnmt3b), of which deregulated activity is linked to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 58 publications
8
122
1
2
Order By: Relevance
“…We show that Dnmt3b is more abundant in EpiSCs compared with ESCs, which in particular could explain the increased deposition of methylation at promoters of germline genes [53]. The expression of the two main Tet enzymes involved in active demethylation and present in ESCs, Tet1 and Tet2, are largely downregulated in EpiSCs.…”
Section: Discussionmentioning
confidence: 74%
“…We show that Dnmt3b is more abundant in EpiSCs compared with ESCs, which in particular could explain the increased deposition of methylation at promoters of germline genes [53]. The expression of the two main Tet enzymes involved in active demethylation and present in ESCs, Tet1 and Tet2, are largely downregulated in EpiSCs.…”
Section: Discussionmentioning
confidence: 74%
“…ICF-specific changes in RNA levels of genes critical for immune function, development, and neurogenesis were identified through the analysis of global expression profiles. [13][14][15][16] Finally, various late-replicating sequences (ie, satellite 2, telomeric repeats, and genes in F-heterochromatin) replicate earlier in ICF than in control cells. 9,11,17 In female ICF cells, genes located in F-heterochromatin lose DNA methylation and escape silencing, and this activation process is associated with a change in their replication timing from late to an earlier stage in the Sphase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DNA methylation at low CpG-density promoters is readily bypassed by activating signals, whereas CpGdense promoters, for which DNA methylation is correlated with significant transcriptional silencing, are rarely methylated in vivo (Metivier et al, 2008;Meissner et al, 2008;Weber et al, 2007). Nonetheless, two recent genome-wide studies have identified genes that rely on DNA methylation for transcriptional silencing in either early embryos or embryonic fibroblasts, and these gene sets are enriched for germline-specific genes (Borgel et al, 2010;Velasco et al, 2010). This observation is consistent with DNA methylation regulating the expression of the germline-specific genes Dazl, Mvh (Ddx4 -Mouse Genome Informatics) and Sycp3 as loss of DNA methylation at these promoters is associated with their transcriptional activation in the developing germline (Maatouk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%